Pengaruh Media Pembelajaran Ubur-Ubur terhadap Numerasi Siswa Kelas II di SDN 06 Ciputat - Inayah Adhani Khoirroni; Nur Avifah Dwi Apriliani; Dhiya Ulhaq Addinillah; Widya Tri Arianti; Destira Ayu Permana; Muhammad Ghulaman Dzaky; Fauzan Al Ansori; Putri Awaliyah; Cahya Adhi Susanto Sumardhi Dwi Putera; Yoga Aditia Ragil (Student Scientific Creativity Journal, 2025)
This study aims to identify the effect of “jellyfish” learning media on numeracy skills for grade II students at SDN 06 Ciputat on multiplication material. Based on initial observation early observations, students had difficulty mastering the concept of multiplication due to monotonous learning procedures and the lack of use of interactive media. The research was conducted through 4 meetings with a simple experimental approach including a pre-test, implementation of the “jellyfish” media, and a post-test to evaluate the learning outcomes. post-test to evaluate the learning outcomes. The results showed that the “jellyfish” media was able to increase students' understanding of multiplication multiplication material, as well as increasing their active involvement in the learning process. learning. The classroom atmosphere became more exciting and interactive, so that students were more focused and motivated. students are more focused and motivated. The teacher also gave a positive reaction to the use of this media, because it can facilitate the delivery of material that is often considered difficult by students. students think is difficult. This study concludes that the “jellyfish” media is jellyfish” media is efficient as a learning tool to improve the numeracy. numeracy skills of grade II students, especially in multiplication material. It is hoped that the same media can be implemented in other materials to support more creative and controversial math learning. support more creative and contextual math learning.